The first records of Kempnyia (Plecoptera: Perlidae) from Central Brazil, with descriptions of new species - Bispo, Pitágoras C.; Froehlich, Claudio G. (Zootaxa, 2004)
Four species of Kempnyia are recorded from Central Brazil representing the first time this genus was found in the area. Two are known species, K. neotropica and K. vanini, and two newly described species, K. oliverai sp. n. and K. goiana sp. n., both belonging to the serrana group.